Pollutants removal from palm oil mill effluent (POME) final discharge using oil palm kernel shell activated carbon in the up-flow continuous adsorption system - Hayawin, Z. Nahrul; Syirat, Z. Bidattul; Ibrahim, M.F.; Faizah, J. Nor; Astimar, A.A.; Noorshamsiana, A.W.; Ropandi, M.; Nursulihatimarsyila, A.W.; Abd-Aziz, S. (Institute for Ionics, 2022)
Biological oxygen demand, color, and suspended solids in palm oil mill effluent (POME) final discharge have a detrimental effect on human health and the environment. Therefore, POME final discharge requires additional treatment before it can be discharged into the river. In this study, POME final discharge was treated using a small-scale up-flow continuous adsorption system with oil palm kernel shell activated carbon (AC-OPKS) as adsorbent material, which improved removal efficiency over the previous batch operation. An effective adsorbent of AC-OPKS was developed using a double-insulated carbonization–activation system with an optimum steam activation temperature of 900 °C, and yield and surface area of 30% and 935 m2/g, respectively. Under optimal working conditions (flow rate = 30 mL/min, treatment time = 3 h, and AC-OPKS dosage = 3 kg), the efficiency of optimized pollutants (BOD, color, and SS) removal was 88.89% using response surface methodology. When compared to the batch treatment, this continuous adsorption treatment significantly reduced BOD, SS, and color intensity from 83, 90, and 97% to 89.70, 89.57, and 97.81%, respectively, with a low concentration of BOD (10.03 mg/L), color (83.20 PtCo), and SS (75 mg/L) recorded at the end of the treatment process. Next, the spent AC-OPKS was regenerated via a thermal regeneration method. Our findings revealed that regeneration time and temperature influenced the regeneration rate and adsorption performance of AC-OPKS. The pollutants removal efficiency of regenerated AC-OPKS optimally prepared at 900 °C for 1 h was 94, 99.43, and 97.36% for BOD, color, and SS, respectively, a higher removal efficiency than virgin AC-OPKS. This study demonstrated that a continuous adsorption system using raw and regenerated AC-OPKS could treat POME final discharge while meeting Malaysia's Department of Environment's standard level.